(untitled) (Bangladesh Journal of Medical Science, 2012)
Hypertension is a major risk factor for various macro and microvascular complications in a patient with diabetes. Control of hypertension is of paramount importance in the care of a diabetes subject. The goals for blood pressure in diabetes subjects are below 130/ 80 mmHg and below 125/75 mmHg if accompanying renal impairment is there. Spironolactone is a medication that has been used to treat high blood pressure since the 1960s. While there is some belief spironolactone reduces blood pressure, there are concerns due to the potential for this drug to cause adverse effects. Previous Meta analysis has shown that spironolactone reduces systolic/diastolic blood pressure by approximately 20/7 mmHg compared to placebo. Spironolactone has also been shown to decrease morbidity and mortality in patients with heart failure. We have tried to emphasize upon the usage of this old but important drug in management of resistant hypertension with reference to its mode of action, benefits and recent studies pertinent to cardiovascular benefits of spironolactone. Data Source:We searched PUBMED and MEDLINE database for relevant articles including key words. References of each article were further reviewed for final synthesis of the manuscript. DOI: http://dx.doi.org/10.3329/bjms.v11i2.8664 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 80-86